2017
DOI: 10.2220/biomedres.38.111
|View full text |Cite
|
Sign up to set email alerts
|

<b>Possible involvement of mucosal-associated invariant T cells in the progression of inflammatory bowel </b><b>diseases </b>

Abstract: Mucosal-associated invariant T (MAIT) cells are innate-like T cells involved in anti-bacterial im-munity. Recent studies have demonstrated that MAIT cells might be implicated in inflammatory bowel diseases (IBDs), but their precise function in IBD remains to be elucidated. We investigated the possible involvement of MAIT cells in the immunopathogenesis of IBDs. Heparinized peripheral blood and biopsy specimens of the colon were collected from 25 patients with ulcerative colitis (UC), 15 patients with Crohn's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 31 publications
(49 reference statements)
9
40
2
Order By: Relevance
“…21 We also reported that MAIT cells accumulated in the inflamed colonic mucosa of IBD patients, although MAIT cells were significantly decreased in the blood of those patients. 27 However, the present study revealed that MAIT cells were significantly decreased in the liver of PBC patients in addition to being reduced in the blood. Consistent with our findings, Jeffery et al recently reported a decreased frequency of MAIT cells in explanted liver tissues of end-stage PBC patients.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…21 We also reported that MAIT cells accumulated in the inflamed colonic mucosa of IBD patients, although MAIT cells were significantly decreased in the blood of those patients. 27 However, the present study revealed that MAIT cells were significantly decreased in the liver of PBC patients in addition to being reduced in the blood. Consistent with our findings, Jeffery et al recently reported a decreased frequency of MAIT cells in explanted liver tissues of end-stage PBC patients.…”
Section: Discussioncontrasting
confidence: 62%
“…In contrast, in patients with multiple sclerosis or RA, MAIT cells accumulate in the inflamed foci of diseases . We also reported that MAIT cells accumulated in the inflamed colonic mucosa of IBD patients, although MAIT cells were significantly decreased in the blood of those patients . However, the present study revealed that MAIT cells were significantly decreased in the liver of PBC patients in addition to being reduced in the blood.…”
Section: Discussionsupporting
confidence: 48%
“…In the case of PSC, and except for the actual inflammation in the liver that could promote gut leakiness, many patients also have concomitant IBD. Interestingly, loss in circulation and accumulation of MAIT cells in inflamed intestine has previously been reported in IBD patients where level of MAIT cells also correlated with disease activity . Yet, we observed no significant differences regarding the MAIT cell loss in patients with PSC and IBD compared to patients with PSC only.…”
Section: Resultscontrasting
confidence: 47%
“…Tominaga et al. also similarly found lower circulating MAIT cell frequencies in their cohort of IBD patients . However, they did not observe NKG2D upregulation in either PB or colonic MAIT cells, due perhaps to an already high expression level of NKG2D in the control cohort or tissues.…”
Section: Mait Cell Surface Molecules Associated With Cytotoxicitymentioning
confidence: 76%
“…Whether MAIT cells express and utilize CD16 is not entirely clear. 48 However, they did not observe NKG2D upregulation in either PB or colonic MAIT cells, due perhaps to an already high expression level of NKG2D in the control cohort or tissues. The potential link between high or heightened expression levels of NKG2D in IBD and cell-mediated cytotoxicity will need to be addressed in the future.…”
Section: Mait Cell Surface Molecules Associated With Cytotoxicitymentioning
confidence: 86%